Literature Review: Factors Affecting Tuberculosis Recurrence in Indonesia - Salma Ainun Nafi’ah (CV. Inara, 2025)
Tuberculosis (TB) remains a significant public health challenge in Indonesia, with relapse contributing substantially to the ongoing disease burden. This systematic literature review aims to identify and synthesize factors affecting TB recurrence in Indonesia, providing insights for targeted interventions. The study employed a comprehensive search across Google Scholar, PubMed, and ScienceDirect using keywords in both English and Bahasa Indonesia, focusing on articles published between 2015 and 2025. A total of 10 primary research articles meeting the inclusion criteria were analyzed, encompassing retrospective, cohort, and cross-sectional designs. Data were extracted on variables such as behavioral, socioeconomic, healthcare, biological, and environmental factors, then synthesized to determine their association with TB relapse. Findings consistently highlight smoking habits, medication non-adherence, low education, inadequate housing ventilation, comorbidities like diabetes, and household contact with TB patients as significant risk factors. Despite heterogeneity in study methodologies, these results underscore the multifaceted nature of TB relapse determinants. The review concludes that integrated strategies addressing behavioral, socioeconomic, and environmental factors are crucial for TB control efforts in Indonesia. Future research should focus on longitudinal and multicenter studies to establish causality and evaluate intervention efficacy. These insights are vital to inform policies aimed at reducing TB recurrence and achieving Indonesia’s goal of TB elimination by 2030.